EFFECTS OF THERMOSONICATION ON WATERMELON RIND-HONEY BEVERAGE - HUSSAIN, N.; AZHAR, N.; RAJOO, S.G.S. (Italian Journal of Food Science, 2019)
This study addressed the recent interest in utilizing waste as source of natural food product to builda safer environment. The sample used was watermelon rind, a by-product of an edible fruit, often ignored for its bland taste. Thermosonication is a method of treating food beverage to improve product quality, but its effects, specifically on rind beverage has not been extensively studied. This study determined the effects of temperature and time (optimization using Response Surface Methodology) on the physicochemical, vitamin C content and microbial load of rind beverages stored under different temperatures for a week. Thermosonication at 65 ºC for 60 min significantly affected juice separation  (stored under 4 ºC in a week)  (11.3%), TSS (12.9  °Brix), the total color difference value (1.7) and microbial load (6.2 log CFU/mL).  Themosonicated rind juice can be stored longer at temperature below  4ºC, which is beneficial to both the consumers and the country at large.